DIAGNOSTIC METHODOLOGY FOR DETERMINING THE LEVEL OF SOCIAL ADAPTATION IN STUDENTS WITH SPEECH DISORDERS (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2026)
This article addresses the diagnostic methodology for determining the level of social adaptation in students with speech disorders. The article analyzes the theoretical foundations of the concept of social adaptation, the impact of speech disorders on social adaptation, and the system of diagnostic criteria and indicators. Additionally, a methodology for assessing the level of social adaptation in students with speech disorders has been developed.